2011
DOI: 10.1111/j.1440-1819.2011.02280.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of feedback from pharmacists in reducing antipsychotic polypharmacy in schizophrenia

Abstract: The objective was to examine effects of active interventions on physician's prescribing of antipsychotic polypharmacy. Prescriptions for patients with schizophrenia at the Centre for Addiction and Mental Health, Canada were collected in 2006 (n = 648) and 2008 (n = 778). During the intervening period, a pharmacist monitored prescriptions with antipsychotic polypharmacy and contacted corresponding prescribers to provide education on risks of polypharmacy. Moreover, educational sessions on polypharmacy were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 7 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…These mechanisms, which have shown some, albeit limited, effectiveness, could target physicians who seem to have the greatest propensity to prescribe high doses or antipsychotic polytherapy (40,41). More broadly, these mechanisms could target entire hospital departments in cases where the data suggest that physicians in these departments tend as a group to systematically keep a greater proportion of their patients on high doses or antipsychotic polypharmacy (42,43).…”
Section: Discussionmentioning
confidence: 96%
“…These mechanisms, which have shown some, albeit limited, effectiveness, could target physicians who seem to have the greatest propensity to prescribe high doses or antipsychotic polytherapy (40,41). More broadly, these mechanisms could target entire hospital departments in cases where the data suggest that physicians in these departments tend as a group to systematically keep a greater proportion of their patients on high doses or antipsychotic polypharmacy (42,43).…”
Section: Discussionmentioning
confidence: 96%
“…For example, a systematic review of interventions for reducing APP concluded that assertive interventions, such as pharmacists' contacting psychiatrists prescribing APP, were more effective than passive interventions, such as education (Hazra et al, 2011;Tani et al, 2013). Further, attitudes towards and experience with switching to monotherapy seem to be important.…”
Section: Discussionmentioning
confidence: 97%
“…There are studies that examined the impact of interventions to convert APP to antipsychotic monotherapy; from educational interventions (Baandrup et al, 2010) to more aggressive ones including active prescription monitoring and direct feedback (Hazra et al, 2011; Laska et al, 1980; Thompson et al, 2008). As passive interventions have shown to have limited efficacy, while more active interventions have a larger effect on decreasing APP (Fleischhacker and Uchida, 2012; Tani et al, in press), the results of this study are potentially helpful in informing more specific approaches, such as identifying specific target doctor populations, concerns that are underestimated, or justifications that are overestimated.…”
Section: Discussionmentioning
confidence: 99%